1994
DOI: 10.1111/j.1469-7610.1994.tb01738.x
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Growth and Mental Development: Evidence for a “Sensitive Period”

Abstract: For many years it has been suspected that severely impaired somatic growth during early postnatal life can be associated with the subsequent impairment of mental abilities. This study aimed to test that hypothesis on the basis of data gathered from a prospective whole population survey of infant development in south London. A year's birth cohort of 1558 full-term singletons was monitored; 47 otherwise healthy cases with serious growth faltering in the first year were recruited. Mental and psychomotor abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
1
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 72 publications
5
74
1
3
Order By: Relevance
“…10,11 The malnutrition in children with FTT can lead not only to impaired growth but also to long-term deficits in intellectual, social, and psychological functioning. 12,13 When FTT is caused by child neglect, certain risk factors are often present. When considering neglect, the pediatrician should assess each risk factor in the context of each family's unique situation.…”
Section: Incidence and Causal Factorsmentioning
confidence: 99%
“…10,11 The malnutrition in children with FTT can lead not only to impaired growth but also to long-term deficits in intellectual, social, and psychological functioning. 12,13 When FTT is caused by child neglect, certain risk factors are often present. When considering neglect, the pediatrician should assess each risk factor in the context of each family's unique situation.…”
Section: Incidence and Causal Factorsmentioning
confidence: 99%
“…Details of the design of the Bavarian Longitudinal Study (BLS) have been described elsewhere (Wolke et al 1994(Wolke et al , 1995aRiegel et al 1995;Wolke 1997a,b) and are only briefly outlined here. All infants born alive in a geographically defined region in south Bavaria between 1st February 1985 and 31st March 1986 and who required admission to one of 17 children's hospitals in this region within the first 10 days of birth comprised the target sample (index children).…”
Section: The Bavarian Longitudinal Study: Cohorts and Designmentioning
confidence: 99%
“…Definite conclusions are difficult to draw owing to shortcomings of earlier studies: many previous investigations included no control groups (Saigal 1991, Saigal et al 1991, Gross et al 1992; often employed variable and arbitrary criteria to define significant cognitive impairment (Wolke et al 1994); were single-centre studies, with epidemiological studies being the exception (Bax 1983, Saigal et al 1991, Veen et al 1991, Robertson et al 1992, Scottish Low Birthweight Study Group 1992, Wolke et al 1994; had no or poor documentation of those lost to follow-up (Aylward et al 1986, Wariyar and Richmond 1989, Leonard et al 1990, Halsey et al 1993, Wolke et al 1995b; and generally included only short follow-up periods Collin et al 1991;Wolke 1991Wolke , 1993McCormick 1992;McCormick et al 1992;Lukeman and Melvin 1993). Lack of attention to study design and methodological factors may have resulted in large underestimations of the adverse cognitive outcome of verylow-birthweight infants (Escobar et al 1991, Ens-Dokkum et al 1992, Gross et al 1992, Wolke et al 1994, Wolke 1997.…”
mentioning
confidence: 99%
“…In one of the few studies that explored the early postnatal period, Emond et al 3 showed that children with the lowest 5% of weight gain from birth to 8 weeks had ∼3-point lower IQ scores than the rest of the cohort (n = 7975). Furthermore, Emond et al 3 and others 29 indicated that weight gain in the first 1 to 2 months after birth is more important for later development than postnatal growth thereafter. However, such research is mostly focused on the relatively small sample of children with the poorest growth who may be clinically categorized as "failing to thrive," whereas the current study involves the normal spectrum of NWG and thus is more representative of the entire population.…”
Section: Discussionmentioning
confidence: 99%